1995
DOI: 10.1139/o95-100
|View full text |Cite
|
Sign up to set email alerts
|

Variety of nonsense suppressor phenotypes associated with mutational changes at conserved sites in Escherichia coli ribosomal RNA

Abstract: To screen for ribosomal RNA mutants defective in peptide chain termination, we have been looking for rRNA mutants that exhibit different patterns of suppression of nonsense mutations and that do not suppress missense mutations at the same positions in the same reporter gene. The rRNA mutations were induced by segment-directed randomly mutagenic PCR treatment of a cloned rrnB operon, followed by subcloning of the mutagenesis products and transformation of strains containing different nonsense mutations in the E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
2

Year Published

1995
1995
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 26 publications
1
27
0
2
Order By: Relevance
“…This bias seems to be due to the use of XL1-Red, because transversions engineered at several of these positions confer strong suppressor phenotypes that would have been easily detected in the screens (see below). Of the 34 mutations recovered, at least six (G886A, U911C, C1054U, C1200U, C1469U, and G1491A) were shown previously to influence the fidelity of elongation (Allen and Noller 1991;Gregory and Dahlberg 1995;Murgola et al 1995;Lodmell and Dahlberg 1997;Pagel et al 1997;Velichutina et al 2000).…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…This bias seems to be due to the use of XL1-Red, because transversions engineered at several of these positions confer strong suppressor phenotypes that would have been easily detected in the screens (see below). Of the 34 mutations recovered, at least six (G886A, U911C, C1054U, C1200U, C1469U, and G1491A) were shown previously to influence the fidelity of elongation (Allen and Noller 1991;Gregory and Dahlberg 1995;Murgola et al 1995;Lodmell and Dahlberg 1997;Pagel et al 1997;Velichutina et al 2000).…”
Section: Resultsmentioning
confidence: 93%
“…Structural studies have shown that C1054 contributes to the A site of the 30S subunit, contacting nucleotide 34 of tRNA and residues of release factors RF1 and RF2 (Ogle et al 2001;Selmer et al 2006;Korostelev et al 2008;Laurberg et al 2008;Weixlbaumer et al 2008). The ability of mutations at position 1054 to increase read-through of stop codons is well established (Hanfler et al 1990;Moine and Dahlberg 1994;Gregory and Dahlberg 1995;Murgola et al 1995;Chernoff et al 1996;Arkov et al 1998), but whether these A-site mutations increase the frequency of the missense errors has been less clear. Murgola and colleagues failed to see effects of these mutations on misreading of several codons in trpA (Pagel et al 1997).…”
Section: Elements Of 16s Rrna Involved In the Fidelity Of Translationmentioning
confidence: 99%
See 1 more Smart Citation
“…Transition (ts)/transversion (tv) ratio of the cereal mt genes also was only two-fifths of that of the ct genes, of which range was between 0.7 and 0.9 for the former and Reference RNA-RNA cross-linking h3, h4, h5, h6, h7a, h7 Pardon and Wagner (1995) Intersubunit bridge h14, h20, h23, h24, h25, h27, h44a, h45 Belanger et al (2002Belanger et al ( , 2004Belanger et al ( , 2005, Ghosh and Joseph (2005), Kubarenko et al (2006) Intersubunit assembly h1, h5, h15, h24, h27, h31, h34 Thanarai et al (1988), Belanger et al (2002Belanger et al ( , 2004Belanger et al ( , 2005, Yassin et al (2005), Kubarenko et al (2006) 30S subunit assembly h39, h40, h41 Ghosh and Joseph (2005) A site h18, h31, h34, h44a Yassin et al (2005) P site h31, h44a, h45 Yassin et al (2005) Translation accuracy h1, h2, h18, h24, h27, h31, h34, h35 Peptide elongation h18, h34, h43 Powers and Noller (1990), Dragon et al (1996), Lafontaine and Tollervey (2001) Peptide chain termination h23a, h34, h44a Murgola et al (1988Murgola et al ( , 1995, Prescott and Goringer (1990), Hanfler et al (1990), Goringer et al (1991), Prescott et al (1991), Gregory and Dahlberg (1995) 1) Helix numbers are cited from Ghosh and Joseph (2005), which correspond to helix numbers encircled by red line in Fig. 2.…”
Section: Features Of Base Substitutions Occurred In the Organellar Gementioning
confidence: 99%
“…located in the helix 34 stem (see Fig. 3) in a region believed to be involved in recognition of peptide chain termination codons (24,25). This region has been directly linked to the decoding site on the ribosome by cross-links from U1052, which is adjacent to m 2 G1207 on the opposite strand to the A site codon of mRNA (26) and from A1196, 11 nucleotides away on the same strand, to the next downstream mRNA codon (10).…”
Section: Substrate Specificity and Mg 2ϩmentioning
confidence: 99%